Destination wedding: uma experiência turística para Foz do Iguaçu - Graciano, Andreia Diedrich (2022)
Understanding the motivations that lead couples to choose a particular destination for their wedding is extremely important to develop market strategies and position itself as a wedding destination. This study aims to understand the motivations that lead couples to choose the city of Foz do Iguaçu for their destination wedding. To achieve the proposed objective, a case study was used through a questionnaire. The analyzes were carried out in a quali/quanti way and the results allowed us to conclude that the cultural factors, in which the travel habits are inserted, drive the decision for the destination wedding and that for the respondents. The predominant factor to choose Foz do Iguaçu as a destination of wedding is the fact that it is a special destination for the couple, as it is the city of origin of one or both of the bride and groom. Also, are attracted for the scenery and landscape, the opportunity for photographic records in the destination, in addition to the tourist infrastructure of the city.